Elucidating the ionic liquid distribution in monolithic SILP hydroformylation catalysts by magnetic resonance imaging. Issue 31 (15th May 2020) - Marinkovic, Jakob Maximilian; Benders, Stefan; Garcia-Suarez, Eduardo J.; Weiß, Alexander; Gundlach, Carsten; Haumann, Marco; Küppers, Markus; Blümich, Bernhard; Fehrmann, Rasmus; Riisager, Anders
Abstract : The action of the liquid catalyst phase in monolithic silicon carbide supported ionic liquid-phase (SILP) Rh-catalysts provide important insight toward industrial upscaling for gas-phase hydroformylation. Abstract : Monolithic silicon carbide supported ionic liquid-phase (SILP) Rh-catalysts have very recently been introduced for gas-phase hydroformylation as an important step toward industrial upscaling. This study investigates the monolithic catalyst system in combination with different impregnation procedures with non-invasive magnetic resonance imaging (MRI). The findings were supported by X-ray microtomography (micro-CT) data of the monolithic pore structure and a catalytic performance test of the catalyst system for 1-butene gas-phase hydroformylation. MRI confirmed a homogeneous impregnation of the liquid phase throughout the full cross-section of the cylindrical monoliths. Consistent impregnations from one side to the other of the monoliths were achieved with a stabilizer in the system that helped preventing inhomogeneous rim formation. External influences relevant for industrial application, such as long-term storage and temperature exposure, did not affect the homogeneous liquid-phase distribution of the catalyst. The work elucidates important parameters to improve liquid-phase catalyst impregnation to obtain efficient monolithic catalysts for industrial exploitation in gas-phase hydroformylation as well as other important industrial processes.